Developmental Benefits of Corruptible Governance where Transparency and Accountability are Held in Dissimulation: The Case of Nigeria - Obera, Jeremiah Johnson O. (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study examined the developmental implications of corruptible governance, where transparency and accountability are exercised through dissimulation, using Nigeria as a case study. It explored why communities celebrate and welcome public officials involved in corruption upon their return from office or prison. The analysis was framed using neopatrimonialism theory. A mixed-method approach was employed, including questionnaires, interviews, document analysis, and newspaper reviews, to ensure a comprehensive investigation. Data were analyzed using weighted means to aid interpretation. The findings revealed that communities often rejoice due to tangible benefits received from perceived corrupt individuals, such as the construction of universities, the recruitment of local youth into security forces, improved infrastructure, world-class hospitals, and uninterrupted electricity supply. The study recommended revitalizing Nigerian welfare systems based on Ubuntu values, emphasizing honesty, integrity, and fairness as a means to counteract corruption.